Industry Payments to Pediatric Orthopaedic Surgeons Reported by the Open Payments Database: 2014 to 2017. Issue 10 (November 2019) - Pathak, Neil; Mets, Elbert J.; Mercier, Michael R.; Galivanche, Anoop R.; Bovonratwet, Patawut; Smith, Brian G.; Grauer, Jonathan N.
Abstract : Background: The Open Payments Database (OPD), mandated by the Sunshine Act, is a national registry of physician-industry transactions. Payments are reported as either General, Research, or Ownership payments. The current study aims to investigate trends in OPD General payments reported to pediatric orthopaedic surgeons from 2014 to 2017. Methods: General industry payments made to pediatric orthopaedic surgeons (as identified by OPD) were characterized by median payment, payment subtype, and census region. As fewer Research and Ownership payments were made, only payment totals for these categories were determined. General payment data were analyzed for trends using the nonparametric Mann-Whitney U test. Results: For General payments, there was an increase in the number of compensated pediatric orthopaedists from 2014 to 2017 (324 vs. 429). Of those compensated, there was no significant change in median payment per compensated surgeon ($201 vs. $197; P =0.82). However, a large percentage of total General payment dollars in pediatric orthopaedics were made to the top 5% of compensated pediatric orthopaedists each year (average 71% of total General industry compensation). For this top 5% group, median General payment per compensated surgeon increased from 2014 ($14, 624) to 2017 ($32, 752) ( P =0.006). A significant increase in median subtype aggregate payment per surgeon was observed in the education ( P <0.001) and royalty/license ( P =0.031) subtypes; a significant decrease was observed for travel/lodging payments ( P =0.01). Midwest pediatric orthopaedists received the highest median payment across all years studied. Few payments for research and ownership were made to pediatric orthopaedists. Four-year aggregate payment totals were $18, 151 and $3, 223, 554 for Research and Ownership payments, respectively. Conclusions: Many expected payments to surgeons to decrease when put under the public scrutiny of the OPD. Not only was this decrease not observed for General payments to pediatric orthopaedic surgeons during the 2014 to 2017 period, but also the median General payment to the top 5% increased. These findings are important to note in the current era of increased transparency. Level of Evidence: Level III.